Supportive care needs of adults living with a peripherally inserted central catheter (PICC) at home: a qualitative content analysis - Rebecca Sharp; Qunyan Xu; ‬‬‬‬‬‬‬‬‬‬‬Robyn Pumpa; Lisa Elliott; Nadia Corsini; Julie Marker; Jodie Altschwager; Alanna Ortmann; Lisa Turner; Lili Jin; Amanda Ullman; Adrian Esterman (BMC, 2024)
Abstract Background Peripherally inserted central catheters (PICCs) are common vascular access devices inserted for adults undergoing intravenous treatment in the community setting. Individuals with a PICC report challenges understanding information and adapting to the device both practically and psychologically at home. There is a lack of research investigating the supportive care needs of individuals with a PICC to inform nursing assessment and the provision of additional supports they may require to successfully adapt to life with a PICC. The aim of this study was to identify the supportive care needs of adults with cancer or infection living with a PICC at home. Method Qualitative, semi-structured interviews were used to identify supportive care needs of adults living with a PICC at home. Participants were recruited from cancer and infectious diseases outpatient units. Two researchers independently analysed transcripts using content analysis. Results A total of 15 participants were interviewed (30-87 years old). There were 5 males and 10 females interviewed, 9 participants had a cancer diagnosis and most lived in a metropolitan area. Many participants lived with a partner/spouse at home and three participants had young children. Participants identified supportive care needs in the following eight categories (i (i) Adapting daily life (ii) Physical comfort (iii) Self-management (iv) Emotional impact (v) Information content (vi) Understanding information (vii) Healthcare resources and (viii) Social supports. Conclusions Adults living with a PICC at home report a broad range of supportive care needs. In addition to practical and information needs, health consumers may also require support to accept living with a device inside their body and to assume responsibility for the PICC. These findings may provide nurses with a greater understanding of individual needs and guide the provision of appropriate supports.